(untitled) (The Pretoria Student Law Review, 2021)
In this article, I intend to focus on the notion of human agency. I argue that the ideologically laden concept of human agency should constitute an ideological and jurisprudential frame from which socioeconomic rights as enshrined in the Constitution should be construed. I seek to ground my submissions on human agency on theoretical perspectives which challenge the present uneven structures of power in South Africa. This essay draws from a multiplicity of disciplines such as Law, Social Sciences and Development Studies. Such a multipronged disciplinary approach to the notion of human agency furnishes a fresh jurisprudential angle to the manner in which socio-economic rights in the Constitution have been construed. The essay is alive to the March 2018 World Bank Report which sets out in clear detail the inequalities that stifle the agency of the majority of the population in South Africa.11 The essay will reconceptualise the notion of human agency in view of socio-economic rights in the South African Constitution. The philosophical contours which undergird my formulation of the concept of human agency will be discussed. In the end, I will provide some reflections regarding the way forward in an effort to engender agency on many South African citizen.